Processing and properties of biphasic calcium phosphates bioceramics derived from biowaste materials - Narumon Lertcumfu (2018)
© 2018 Trans Tech Publications, Switzerland. Properties of biphasic calcium phosphates bioceramics derived from biowaste materials were investigated. The hydroxyapatite (HA) powder was synthesized from bovine bone via thermal treatment while β-tricalcium phosphate (β-TCP) powder was synthesized from mussel shells via solid state solution. Pure HA and β-TCP were successful obtained. The HA and β-TCP were mixed together and sintered at 1100-1350°C. The effects of the sintering temperature and the ratio of HA/β-TCP on the properties of the studied samples were investigated. The sintering temperature at 1250°C presented the maximum value of density and hardness. X-ray analysis of BCP ceramics sintered at 1250°C presented multiple phases of calcium phosphate. Average grain sizes of the studied samples decreased as the ratio of HA increased.